Risk Factors for Preterm Birth: A Comprehensive Review of Current Evidence - Julia Piekarska; Justyna Maria Solarz; Jakub Tomasz Wawrzyńców; Weronika Cyrkler; Jakub Robak; Stanisław Telega; Paweł Bollin; Urszula Szymczak; Wojciech Wiesław Lachór; Monika Barbara Solarz (Quality in Sport)
Preterm birth, defined as the termination of pregnancy before the completion of 37 weeks of gestation, remains one of the most critical challenges in contemporary perinatal care. High neonatal mortality rates, along with frequent neurological, respiratory, and developmental complications, underscore the importance of identifying risk factors associated with preterm labor. The aim of this review was to comprehensively synthesize current scientific evidence on the multifactorial etiology of preterm birth, encompassing biological, immunological, genetic, environmental, and socio-economic determinants. A systematic literature search was conducted in PubMed during January and February 2025, covering peer-reviewed publications from 2020 to 2024. Included in the analysis were meta-analyses, cohort studies, case-control studies, systematic reviews, and population-based analyses.